P1-2-07. Relationship between Saccadic Eye Movements and Higher Brain Function in the elderly. Issue 5 (May 2018) - Hashimoto, Shingo; Hase, Kimitaka; Tanemura, Rumi; Nakamura, Kae
Abstract : Saccadic eye movements (SEM) are used as a biomarker for psychiatric disorders. However, the relationship between SEM and higher brain function has not been fully elucidated. Therefore, we examined SEM during the Trail Making Test part A (TMT-A), a neuropsychological test of visual attention and processing speed, and assessed the correlation between the frequency of SEM during TMT-A and neuropsychological test results. The eye movements of 43 elderly subjects (>65 y/o, mean 72.4 y/o), with no history of neuropsychiatric disorders, were measured using eye tracking glasses (SensoMotoric Instruments, Germany). Eye movements of more than 1.6 degrees/s were judged to be SEM. We found a significant inverse correlation between the frequency of SEM during TMT-A and the time required to complete TMT-A (r = −0.402, p = 0.008). We found a positive correlation with the Backward block-tapping span (r = 0.371, p = 0.015), a neuropsychological test of spatial working memory, and the Japanese version of the Montreal Cognitive Assessment (r = 0.301, p = 0.021). The lower frequency of SEM during TMT-A reflected lower processing speeds and spatial working memory, which may lead to poorer performance on neuropsychological tests. This result indicates that the frequency of SEM during TMT-A might be an informative biomarker for attention and cognitive function in the elderly.